Daptomycin and Ampicillin Combination for Treatment of Enterococcus faecalis Endocarditis. Issue 4 (July 2015) - Sierra-Hoffman, Miguel; Iznaola, Oscar; Lamp, Kenneth C.; Mohr, John F.; Winn, Richard E.
Abstract : Abstract: Aminoglycosides in combination with penicillins or glycopeptides have been shown to provide synergistic killing and are recommended for the treatment of enterococcal endocarditis. Because of the ototoxicity and nephrotoxicity properties of aminoglycosides, aminoglycoside-sparing regimens for the treatment of enterococcal endocarditis are needed. Daptomycin is an antimicrobial with bactericidal activity against Enterococcus faecalis . We report a case series of 5 patients treated with a combination of daptomycin and ampicillin.